Growth and reproduction data of Plesionika narval (Decapoda, Caridea, Pandalidae) off the Island of Ustica (southern Tyrrhenian Sea) - ARCULEO, Marco; LO BRUTTO, Sabrina (Crustaceana, 2011)
We here report some data on the biology and population structure of Plesionika narval (Fabricius, 1787) captured along the coast of the island of Ustica in the southern Tyrrhenian Sea. Specimens were collected monthly from January to October 2000 using commercial traps at depths ranging from 15 to 100 metres. The carapace length (CL) of females ranged between 7.0 and 26.0 mm, and between 7.0 and 17.0 mm for males. Three modes were identified in the cumulative frequency distribution for females but only two for males. In females, the third modal value was observed only at the deeper sample sites. The Von Bertalanffy growth parameters and performance index φ were K = 0.65 y−1, CL∞ = 27.4 mm CL and φ = 2.62 for females, and K = 0.71 y−1, CL∞ = 17.8 mm CL and φ = 2.28 for males. Ovigerous females were found during the entire period of the investigation, indicating that this species spawns all year round. We compared our results with other data recorded in the literature.